2008
DOI: 10.1016/j.sna.2007.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Hamiltonian modelling of magnetic shape memory alloy based actuators

Abstract: This paper proposes an application of the Lagrangian formalism and its Hamiltonian extension to design, model and control a mechatronic system using Magnetic Shape Memory Alloys. In this aim, an original dynamical modelling of a Magnetic Shape Memory Alloy based actuator is presented. Energy-based techniques are used to obtain a coherent modelling of the magnetical, mechanical and thermodynamic phenomena. The Lagrangian formalism, well suited in such a case, is introduced and used to take into account the dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 7 publications
(11 reference statements)
0
41
0
1
Order By: Relevance
“…Nevertheless in practical applications and for specific conditions, some reductions can be made (isothermal process on 2D motions) and in such a case, the usefulness of the model is shown. For example, in the paper [13], an extension of the quasi-static isothermal model to the dynamical case was made, including the magnetic circuit creating the magnetic field and a dynamical load applied to the MSMA sample. A thermodynamic approach with hamiltonian modeling was used by the authors to design actuators [13] and new control laws [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless in practical applications and for specific conditions, some reductions can be made (isothermal process on 2D motions) and in such a case, the usefulness of the model is shown. For example, in the paper [13], an extension of the quasi-static isothermal model to the dynamical case was made, including the magnetic circuit creating the magnetic field and a dynamical load applied to the MSMA sample. A thermodynamic approach with hamiltonian modeling was used by the authors to design actuators [13] and new control laws [14].…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the paper [13], an extension of the quasi-static isothermal model to the dynamical case was made, including the magnetic circuit creating the magnetic field and a dynamical load applied to the MSMA sample. A thermodynamic approach with hamiltonian modeling was used by the authors to design actuators [13] and new control laws [14]. Moreover, the thermodynamical approach proposed in this paper to model a specific MSMA can be easily extended to other materials, such as future MSMA monocristals and polycristals.…”
Section: Resultsmentioning
confidence: 99%
“…4 (a) and presented in Gauthier et al (2008), the different energy functions can be divided into parts as shown in Fig. 4 consider the magnetization energy stored in the iron core, at low magnetic field the behaviour is nearly linear: B = µH or M = χH with B, H, and M , being the magnetic induction field, the magnetic excitation field and the magnetization in the core of the magnetic circuit.…”
Section: Application To Msma Based Actuatormentioning
confidence: 99%
“…8, these three internal variables are inspired by the microstructure of MSMA sample (NiMnGa material) and are used to clarify the electromechanical energy conversion inside this smart material. The constitutive equation of the independent internal variable ξ describes the irreversible behaviour of MSMA and is used to calculate the dissipation function D. In Gauthier et al (2008), a simple hysteresis loop was chosen, where threshold and rate were identified experimentally (see Fig. 9).…”
Section: Application To Msma Based Actuatormentioning
confidence: 99%
“…All other variables are material parameters and can be experimentally identified (see [31]). In this expression, the magneto-thermo-mechanical coupling is expressed by the choice of the internal variable z.…”
Section: Quasi-static Modeling Of Msmamentioning
confidence: 99%